Queer critical intersections with ecology and religion : Review of Bauman, W. A. (Ed.) (2018). Meaningful Flesh: Reflections on Religion and Nature for a Queer Planet. Goleta, California: Punctum Books - Ibarra Cordero, Andrés (2021)
Religion and Nature are queer phenomena; that is the premise of Meaningful Flesh, a transdisciplinary collection of critical essays that examine the academic intersections of queer theory, religious studies, and ecocriticism. It has been a long time since pioneer scholars, such as John Boswell (1981) and Marcella Althaus-Reid (2002), explored the history of religious traditions from a gay and lesbian studies perspective. Nevertheless, very few scholars have ventured into the fields of religion and ecology from a queer critical view. Except maybe for Daniel T. Spencer’s groundbreaking book Gay and Gaia (1996), a pioneer scholarly endeavor to incorporate insights of ecology, environmental ethics and liberation theologies, queer scholars have rarely examined the intersection of religion and ecology. Indeed, these disciplines rarely come across with each other. Therefore, cultivating the skill of transdisciplinary thinking, the chapters of this volume generate an intellectual ecosystem in which scholars can strengthen the background and general knowledge of the interrelationships among religion, nature, and understandings of queer phenomena. As such, Meaningful Flesh becomes distinctive in its academic scope and novel critical insights. While each essay creates a unique contribution, the notion of “performativity” links them in fascinating queer ways.